Dialectic between Women's Freedom and Free Women in History "The Experience of the Armed Struggle in North Kurdistan as an Example" - Abdulkarim, Prof. Salam (Sulaimani Journal for Humanities, 2026)
There is a great cognitive debate on the concept of freedom in general and the freedom of women and free women in particular, so that each intellectual and political direction has its own definition and understanding of these concepts. Some associate women's freedom with physical freedom, but others describe women's freedom in its philosophical and spiritual sense. The aim of such understandings is to produce a new concept that embodies itself in free women, in the sense of who is a free woman? Meanwhile, the Kurdish armed struggle in North Kurdistan is an important experience in history to follow and study the dialectic between the concepts of women's freedom and free women, because theoretically and then practically produced in this struggle Kurds in this part of Kurdistan have their own intellectual and political views on women's freedom and free women. This paper attempts to investigate the dialectic between the concept of women's freedom and free women in history. For this purpose, the Kurdish armed experience in North Kurdistan is taken as an example based on a number of scientific sources in order to reach objective and scientific conclusions, in order to analyze the dialectic of women's freedom and free women.
Keywords: Women; Freedom; Dialectics; North Kurdistan; History